Diaphragm ultrasound as a predictor of successful extubation from mechanical ventilation - DiNino, Ernest; Gartman, Eric J; Sethi, Jigme M; McCool, F Dennis (Thorax, 2014)
Introduction The purpose of this study was to evaluate if ultrasound derived measures of diaphragm thickening, rather than diaphragm motion, can be used to predict extubation success or failure. Methods Sixty-three mechanically ventilated patients were prospectively recruited. Diaphragm thickness (tdi) was measured in the zone of apposition of the diaphragm to the rib cage using a 7–10 MHz ultrasound transducer. The percent change in tdi between end-expiration and end-inspiration (Δtdi%) was calculated during either spontaneous breathing (SB) or pressure support (PS) weaning trials. A successful extubation was defined as SB for >48 h following endotracheal tube removal. Results Of the 63 subjects studied, 27 patients were weaned with SB and 36 were weaned with PS. The combined sensitivity and specificity of Δtdi%≥30% for extubation success was 88% and 71%, respectively. The positive predictive value and negative predictive value were 91% and 63%, respectively. The area under the receiver operating characteristic curve was 0.79 for Δtdi%. Conclusions Ultrasound measures of diaphragm thickening in the zone of apposition may be useful to predict extubation success or failure during SB or PS trials.